PERSEPSI MASYARAKAT TERHADAP KEBERADAAN GAJAH DI DESA TEGAL YOSO KABUPATEN LAMPUNG TIMUR - Winarno, Gunardi Djoko; Sugianto, Lisa Mutiara (Fakultas Kehutanan Universitas Winaya Mukti, 2023)
The public's perception of the existence of elephants, which are often on community cultivated land and outside forest areas, is very important to study, as a guide in mitigating conflicts between humans and elephants. This conflict has economic, socio-cultural and ecological impacts. This research aims to analyze the economic, social and cultural impacts of human-elephant conflict, based on community perceptions. This research was carried out in Tegal Yoso Village, East Lampung Province. This research method was carried out by means of field surveys and interviews with the community as many as 30 respondents. The results of this research show that people understand that elephants are considered protected animals, but elephants are also destroyers of people's crops or plant pests. The economic impact that occurs is the size of the potential harvest of agricultural crops, especially corn, rice and cassava. This conflict causes crop failure losses of 30% -100% of agricultural crops. On the other hand, elephant activity results in damage to work huts, lookout towers, human injuries, broken bones and even fatalities. This conflict also resulted in socio-cultural impacts on the community, such as horizontal conflicts between communities and vertical conflicts, namely between the community and Way Kambas National Park officials. On the other hand, the community agrees that there is social responsibility in the form of mutual cooperation in controlling elephant attacks. Another effort that has been implemented is the construction of embankments and canals. The community agrees that efforts to resolve the conflict between elephants and humans continue to be made. The community hopes that Way Kambas National Park can provide the latest innovations in overcoming conflict.Keywords: conflict, economic and social-cultural, impact, elephants, peopleÂ